Outcome of Very Low and Low Birth Weight Infants with Esophageal Atresia: Results of the Turkish Esophageal Atresia Registry - KIYAN, GÜRSU (GEORG THIEME VERLAG KG, 2021)
Introduction The data of the Turkish Esophageal Atresia Registry (TEAR) was evaluated to define the outcome of very low birth weight (VLBW) and low BW (LWB) infants with esophageal atresia (EA). Materials and Methods The data registered by 24 centers between 2014 and 2018 were evaluated for demographic features, prenatal findings, associated anomalies, surgical treatment, and outcome. Patients were enrolled in three groups according to their BWs (VLBW <1,500g), LWB=1,500-2,500g), and normal BW (NBW; >2,500g). Results Among the 389 cases, there were 37 patients (9.5%) in the VLBW group, 165 patients (42.4%) in the LBW group, and 187 patients (48.1%) in the NBW group. Prenatal diagnosis rates were similar among the three groups (29.7, 34.5, and 24.6%, respectively). The standard primary anastomosis was achieved at a significantly higher rate in NWB cases than in the other groups ( p <0.05). In patients with tracheoesophageal fistula (TEF), patients of the NBW group had significantly higher rates of full oral feedings, when compared with VLBW and LBW cases ( p <0.05). At the end of the first year, when we evaluate all patients, the number of cases with fistula recanalization and esophageal anastomotic strictures (AS) requiring esophageal dilatation was similar among the groups. The weight and height measurements at 6 months and 1 year of age of the survivors were similar in all the groups. The overall mortality rate was significantly higher in the VLBW and LBW groups, when compared with the NBW patients, even in patients with tension-free anastomosis ( p <0.05). The incidence of the associated anomalies was 90.6% in cases with mortality, which was significantly higher than in survivors (59.6%; p <0.05). According to Spitz's classification, the survival rate was 87.1% in class I, 55.3% in class II, and 16.7% in class III. The most common causes of mortality were associated with cardiovascular diseases, pneumonia, and sepsis. Conclusion The national data of TEAR demonstrates that the developmental and feeding parameters are better in NBW patients. Although VLBW patients have higher risk of developing fistula canalization than the LBW and NBW groups, long-term complications, such as anastomotic strictures, weight, and height values, after 1 year are similar in both groups. According to our results, associated anomalies and LBWs are still significant risk factors for mortality in cases with EA.
Keywords: esophageal atresia; national registry; very low birth weight; low birth weight; SINGLE-CENTER EXPERIENCE; RISK-FACTORS; ATRESIA/TRACHEOESOPHAGEAL FISTULA; TRACHEOESOPHAGEAL FISTULA; PROGNOSTIC CLASSIFICATION; PRENATAL-DIAGNOSIS; PRIMARY REPAIR; PREVALENCE; SURVIVAL; CHILDREN